2020
DOI: 10.7717/peerj.9770
|View full text |Cite
|
Sign up to set email alerts
|

The effect of music on the perception of outdoor urban environment

Abstract: Music may modify the impression of a visual environment. Most studies have explored the effect of music on the perception of various service settings, but the effect of music on the perception of outdoor environments has not yet been adequately explored. Music may make an environment more pleasant and enhance the relaxation effect of outdoor recreational activities. This study investigated the effect of music on the evaluation of urban built and urban natural environments. The participants (N = 94) were asked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…For instance, an audiovisual experiment on car simulation (Iwamiya, 1997) found that listening to music makes landscapes appear more pleasant than without music and that they are generally evaluated congruently with musical features. This has also been shown in various field experiments (Ehret et al, 2021;Franěk et al, 2020;Yamasaki et al, 2015). The interplay between musical features and environmental features (e.g., natural or urban environment, valence of atmosphere) is crucial for how perception is altered.…”
Section: The Impact Of Music Listening and Emotions On Visual Perceptionmentioning
confidence: 56%
See 3 more Smart Citations
“…For instance, an audiovisual experiment on car simulation (Iwamiya, 1997) found that listening to music makes landscapes appear more pleasant than without music and that they are generally evaluated congruently with musical features. This has also been shown in various field experiments (Ehret et al, 2021;Franěk et al, 2020;Yamasaki et al, 2015). The interplay between musical features and environmental features (e.g., natural or urban environment, valence of atmosphere) is crucial for how perception is altered.…”
Section: The Impact Of Music Listening and Emotions On Visual Perceptionmentioning
confidence: 56%
“…This suggests that affective evaluations are more likely to be influenced by the emotional state of the perceiver than cognitive evaluations, as already noted by Russell et al (1981). Consequently, cognitive evaluations are more likely to be influenced by the environment itself and objective features than by the individual's emotional state or by music (Franěk et al, 2020).…”
Section: Musical Impact On Affective Vs Cognitive Rating Dimensions O...mentioning
confidence: 64%
See 2 more Smart Citations
“…Contextual factors cannot be fully considered and accounted for when measuring in a laboratory. Contextual factors known to impact on real-world walking speed and cadence include the weather [16], the walkability of the environment, the purpose of the journey, the commonality of the route, elevation (gradient) of pathway [17]. Contextual factors can be recorded and accessed through smartphone data.…”
Section: Discussionmentioning
confidence: 99%